2017
DOI: 10.1038/srep40935
|View full text |Cite
|
Sign up to set email alerts
|

Three novel ANO5 missense mutations in Caucasian and Chinese families and sporadic cases with gnathodiaphyseal dysplasia

Abstract: Gnathodiaphyseal dysplasia (GDD; MIM#166260) is an autosomal dominant syndrome with characteristic cemento-osseous lesions of jawbones, bone fragility, and diaphyseal sclerosis of tubular bones. To date, only five mutations in the proposed calcium-activated chloride channel ANO5/TMEM16E gene have been identified. In this study, we describe two families and two singular patients with three new mutations. One Caucasian family with seven affected members exhibited frequent bone fractures and florid osseous dyspla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(43 citation statements)
references
References 29 publications
4
38
1
Order By: Relevance
“…Riminucci et al reported aberrant calcification and thickening of vessel walls and narrowing of the lumens . However, these findings were not reported in the other two articles . In our study, the bone trabeculae were poorly formed and cementum‐like.…”
Section: Discussioncontrasting
confidence: 78%
See 3 more Smart Citations
“…Riminucci et al reported aberrant calcification and thickening of vessel walls and narrowing of the lumens . However, these findings were not reported in the other two articles . In our study, the bone trabeculae were poorly formed and cementum‐like.…”
Section: Discussioncontrasting
confidence: 78%
“…There are three articles reporting the histological features of GDD . All agreed that the pathology shows fibro‐osseous lesions with scattered psammomatoid bodies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…In humans, ANO3 has been linked to craniocervical dystonia, a disorder affecting muscles of the upper limbs, neck and larynx . Furthermore, ANO5 has been associated with disorders involving both bone and muscle weakness in humans . As a result, both ANO3 and ANO5 appear to warrant further exploration in the horse – particularly with regard to genetic studies of DLC and other URT disorders.…”
Section: Discussionmentioning
confidence: 99%